THE IMPACT OF DIGITIZATION ON ADMINISTRATIVE CREATIVITY: A FIELD STUDY IN AN ALGERIAN PUBLIC INSTITUTION - Zedira Khammar; Nour El Houda Kouachi; Zahia Boumedjane; Hichem Amejouj; Said Mabrouki (International Journal of Innovative Technologies in Social Science, 2025)
This study aims to explore the impact of digitalization on administrative creativity, approaching the topic from two integrated perspectives: theoretical and applied. Theoretical in nature, it addresses the concepts of digitalization, its types, and challenges, in addition to providing a detailed presentation of the concept of administrative creativity, its characteristics, and basic theories. The field study is based on a case study of Mohamed Boudiaf Hospital in the province of Oum El Bouaghi, where the impact of digitalization components (such as digital transformation, cloud storage, and electronic applications) on the dimensions of administrative creativity (efficiency, cooperation, and adaptation) was analyzed. The study aims to assess the organization’s capacity to adopt digitalization, diagnose the reality of administrative creativity within the organization, and identify the most significant challenges and difficulties associated with both. The researchers used a structural-functional approach in their methodological framework, utilizing data collection tools such as questionnaires and interviews with a sample of administrative staff and physicians working at the facility.